2017
DOI: 10.1371/journal.pntd.0005941
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site cholera surveillance within the African Cholera Surveillance Network shows endemicity in Mozambique, 2011–2015

Abstract: BackgroundMozambique suffers recurrent annual cholera outbreaks especially during the rainy season between October to March. The African Cholera Surveillance Network (Africhol) was implemented in Mozambique in 2011 to generate accurate detailed surveillance data to support appropriate interventions for cholera control and prevention in the country.Methodology/Principal findingsAfrichol was implemented in enhanced surveillance zones located in the provinces of Sofala (Beira), Zambézia (District Mocuba), and Cab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…The majority of studies were both age- and sex-matched analyses, but a subset assessed risk for cholera based on these characteristics. Fifteen studies assessed differential risk by age [ 13 , 26 , 32 , 33 , 35 , 47 , 53 , 70 , 82 , 85 , 97 , 101 , 104 , 110 , 118 ], 10 of which implemented a multivariable model [ 26 , 32 , 33 , 35 , 82 , 97 , 101 , 104 , 110 , 118 ]. Age was measured heterogeneously and findings were mixed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies were both age- and sex-matched analyses, but a subset assessed risk for cholera based on these characteristics. Fifteen studies assessed differential risk by age [ 13 , 26 , 32 , 33 , 35 , 47 , 53 , 70 , 82 , 85 , 97 , 101 , 104 , 110 , 118 ], 10 of which implemented a multivariable model [ 26 , 32 , 33 , 35 , 82 , 97 , 101 , 104 , 110 , 118 ]. Age was measured heterogeneously and findings were mixed.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies found that younger patients were at higher risk for cholera [ 26 , 35 , 101 , 110 ], and 1 study found that older children had higher risk than children <1 year old [ 32 ]. Other studies, however, found older people to be at higher risk [ 33 , 97 ], or no difference in risk based on age [ 82 , 104 , 118 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations